Kantian explanation of the aesthetic judgment - Henrich, Dieter; Carvajal Correa, Carlos (Estudios de Filosofía, 1992)
Kant’s Critique of Judgment has generally been considered a turning point in the history of the Aesthetics and Philosophy of art. It gathers and reconstructs the results of the analysis of aesthetic predicates and the aesthetic attitude that emerged in the schools of Leibniz and Locke, as formulated by philosophers such as Baumgarten and Sulzer on the one hand and Hume and Burke on the other. But he also raised aesthetic theory to a new level, integrating it into the system of a new epistemology that Kant had successfully worked on in the Critique of Pure Reason, based on the consideration according to which, what we call reason consists of a complex interaction of various epistemic operations. In order to understand what "reason" achieves, one must attend to the operations from which such achievement proceeds. In addition, we must pay attention to the sources in which these operations originate and the principles or rules that guide them. The Critique of Judgment discovers such a source with respect to the appreciation of the beautiful (and the sublime). In this way it has proven to be capable of separating aesthetic judgments from other kinds of judgments, at the same time that it preserves its claim to originate in reason as such and in activities that are intertwined with those on which all our knowledge of the world depends. These judgments certainly do not express knowledge. But his claim is equally justified because it is based on exactly the same activities that give rise to knowledge, albeit in a peculiar interactive use. Through this point of view, Kant provides for the first time tools for the establishment of the aesthetic attitude as independent and autonomous, and thus as the foundation for a conception of art as a primordial way of being related and situated within our world, which cannot be superseded or surpassed by other realizations of man’s rational capacities.